Diagnóstico y propuesta de un manual orgánico y funcional para el cuerpo de bomberos del cantón Sucúa de la provincia de Morona Santiago, para el año 2015 - Elizalde Atzuchi, Eddy Favian (2016)
The purpose of this research is to implement an organizational and functional manual for the Cuerpo de Bomberos de Sucúa using tools to identify existing gaps in current procedures and simplification in order to have a more efficient human capital. The theme uncovered a series of conceptions, definitions, ideas and judgments concerning the organizational structure of public companies; the importance, classification and application of organizational and delve into the generalities of the institution under investigation and in legal precepts who assist the investigation. It is considered a form of intervention project, covered in the documentary, descriptive and field research; analytical, inductive and deductive method is applied in a quantitative study, to understand and define the nature of the conflict situation; research techniques used are the interview and the survey with their instruments; the script and the questionnaire, to be widely applicable and easy to use, the resulting data were tabulated and plotted for better interpretation and understanding. The proposal to implement a manual and Organic Functional generated by the shortcomings and weaknesses that externalizes the institution in the development of their daily work. The investigation detect slow internal processes, insufficient technical infrastructure in administrative, labor instability and an obsolete regulation, in such a situation the need to analyze the procedures and functions that cause conflict in the work developed by the Institution came off. The proposal aims to give greater flexibility to the document, which allows the implementation, objectives, policies, goals and procedures to achieve the efficiency and productivity of the institution.